Iron (Fe) dissolved in soil pore water collected from 16 drained thaw lake basins near Barrow, Alaska, 2011 - D. A. Lipson (Arctic Data Center, 2013)
Soil pore water was collected from 16 drained thaw lake basins near Barrow, Alaska (AK) and analyzed colorimetrically for Fe(II) and Fe(III). Three to five basins of each age class (as determined by Hinkel and others) were chosen. Transects were established in each basin (most were 30 meter (m) long, except the plots established in 2010, which were up to 72 m long). Samples (generally five per transect) were collected into vacutainers from Rhizon soil water samplers, preserved with a drop of hydrochloric acid (HCl), and analyzed using 1,10-phenanthroline, with and without ascorbate for total Fe and Fe(II), respectively. Fe(III) was determined by difference.